Enabling good transition processes from child to adult medical care: a study protocol - Ravnbøl, Camilla Ida; Altweck, Laura; Schmidt, Silke; Bistrup, Lene; Borgwardt, Stefan; Arnfred, Sidse Marie; Jeppesen, Pia; von Bismarck, Philipp; Nellegaard, Julie Bork; Prehn-Kristensen, Alexander; Colic, Ada (Frontiers in Health Services, 2025)
Hundreds of patients each year transfer from child to adult medical care when they become adults. The transfer in health care comes with a risk of interrupted treatment or a failure to follow treatment properly, which can have serious consequences for the physical and mental health and well-being of the young person, and for their future ability to engage in education, work or social life. The Child to Adult Transition project (CAT) is a cross-country and inter-disciplinary innovation and research project that aims to address this pertinent topic. CAT focuses on young people in rheumatology and mental health care in Denmark and Germany and develops transition programmes to support young persons and their parents in the transfer from child to adult medical care, while exploring how young people experience and reflect on this transition and their experiences of the CAT programs. The CAT study has a longitudinal, mixed-methods study design, surveying young patients (age 15–25 years), their parents/guardians, and health-care professionals via interviews (individual or group), field observations, and/or online surveys. At baseline, interviews will be conducted with 24–68 adolescents and young adults, 24–68 parents/guardians, and 24–68 health-care professionals in both countries and across disciplines. 13–14 observations will be made in three settings and, at baseline, 400 adolescents and young adults will receive the survey. Interviews and surveys will be repeated after six and 12 months. The study will focus on topics such as everyday life as a young patient, transition experiences, somatic, and mental health, and quality of life. The CAT project period runs from January 2023 to December 2025. Recruitment to the CAT study is ongoing and all ethical approval have been obtained from the different departmental sites and ethical committees. The project combines different medical disciplines (child, adolescent and adult rheumatology and mental health), academic disciplines (medicine, anthropology and psychology) as well as countries (Germany, Denmark). It also combines person-groups (young persons, parents, professionals) and methods (interviews, observations, surveys). This approach provides new perspectives on the medical, psychological and anthropological aspects of the complex nature of the medical transfer. The findings will feed into the guidelines on transitional care, can also be used in other medical disciplines, and can be prepared as popular publications and other media enabling a broader audience to be reached.The study protocol is registered on the Open Science Framework: https://osf.io/vdy9p